2009
DOI: 10.1007/s00264-009-0886-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective COX-2 inhibitor versus nonselective COX-1 and COX-2 inhibitor in the prevention of heterotopic ossification after total hip arthroplasty: a meta-analysis of randomised trials

Abstract: Whether selective cyclo-oxygenase-2 (COX-2) inhibitors are equally effective compared to nonselective NSAIDs for the prevention of heterotopic ossification (HO) after total hip arthroplasty (THA) is still unclear. We carried out a comprehensive search strategy, in which only randomised controlled trials were included. Two reviewers independently assessed methodological quality and extracted outcome data. Analyses were performed using Stata version 10.0. Four eligible randomised controlled trials totalling 808 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
3
38
0
1
Order By: Relevance
“…Meta-analyses on randomised clinical trials on the efficacy of selective COX-2 inhibitors and non-selective NSAIDS found both medications equally effective in the prevention of HO after THA [10]. Considering the side effects of nonselective NSAIDs, selective COX-2 inhibitor was recommended as the preferable medication for the prevention of HO after THA [9,10,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses on randomised clinical trials on the efficacy of selective COX-2 inhibitors and non-selective NSAIDS found both medications equally effective in the prevention of HO after THA [10]. Considering the side effects of nonselective NSAIDs, selective COX-2 inhibitor was recommended as the preferable medication for the prevention of HO after THA [9,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…This selective COX-2 inhibitor is associated with significantly fewer gastrointestinal side effects [9] and is therefore recommended [10]. In a prospective two-stage study design for phase 2 clinical trials, we investigated the efficacy of etoricoxib 90 mg once daily oral dose for seven days in a small sample of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological interventions in the form of NSAID's, COX-2 inhibitors, 30 bisphosphonates, 31 or anti-coagulants such as warfarin 32 are currently used in the early stages of HO or MO as prophylactics. All these treatments carry with them potentially harmful side-effects such as adverse gastro-intestinal and cardiovascular effects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Так, в 2009 г. опуб-ликовано исследование D. Xue и соавт. [70] -метаанализ 4 РКИ, в которых сравнивали эффективность для профила-ктики ГО сНПВП и нНПВП. Препараты назначали на 7-14 дней пациентам, перенесшим ортопедические опера-ции (n=808).…”
Section: субхондральная кость Nf-кв/rankl-зависимая активизация остеоunclassified